The Role of Formative Assessment in Enhancing Students’ Numeracy Literacy: A Qualitative Evaluation - Reza Oktiana Akbar (Jurnal Penelitian Pendidikan IPA, 2025)
In the context of 21st-century education, numeracy literacy is a crucial competency that supports students’ critical thinking and problemsolving abilities across various disciplines. However, many students continue to struggle with applying mathematical concepts in real life situations. This study aims to explore the role of formative assessment in enhancing students' numeracy literacy in secondary school settings. Utilizing a qualitative approach, data were collected through classroom observations, semi-structured interviews with teachers and students, and documentation analysis. The participants consisted of three mathematics teachers and twelve students from different grade levels in a public secondary school. Thematic analysis was employed to identify key patterns in the data. The findings reveal that formative assessment strategies such as real-time feedback, reflective questioning, and peer assessment significantly contributed to the development of students’ numeracy skills. Teachers reported improved student engagement and better diagnostic understanding of learning gaps, while students demonstrated increased confidence and ability to apply mathematical reasoning. The study concludes that formative assessment is an effective pedagogical tool for supporting numeracy literacy and recommends its integration into daily classroom practices to foster a deeper understanding of mathematical concepts.